Analisis Kontribusi Pendapatan Asli Daerah terhadap Pendapatan Daerah Kabupaten Konawe Selatan - La Jejen (Politeknik Baubau, 2022)
This study is entitled the analysis of regional income to the regional income of South Konawe Regency. This study aims to study and analyze regional own-source revenue towards the regional income of South Konawe Regency.This research uses descriptive quantitative analysis, in which this study illustrates the regional finance to regional income using numbers by comparing the figures obtained. The results showed that the contribution of regional own-source revenue (PAD) to the Regional Revenue of South Konawe Regency in the period 2007-2017 was relatively low. Contribution of Local Own Revenue Components (PAD) such as Regional Tax, Regional Retribution, BUMD profit, and others. Regional original income to the Regional Revenue of South Konawe Regency in the period 2007-2017 is still relatively low.